ENGAGING YOUNG MINDS: EFFECTIVE STYLES OF TEACHING ENGLISH TO YOUNG LEARNERS - Ahmedova Nodira Djavadullaevna (Bright Mind Publishing, 2025)
This article explores effective teaching methods for young learners in English language education. It highlights various approaches, including play-based learning, storytelling, and Total Physical Response (TPR), which cater to children's curiosity and short attention spans. The paper emphasizes the importance of phonics and early literacy, integrating technology, and using multisensory learning techniques to enhance engagement. Additionally, it discusses culturally responsive teaching to ensure inclusivity. The study underscores the need for a positive and interactive learning environment, regular feedback, and diverse teaching strategies to foster a lifelong love for the English language.
Keywords: Young learners, play-based learning, storytelling, Total Physical Response (TPR), phonics, technology integration, multisensory learning, culturally responsive teaching, early literacy, interactive learning.